2020
DOI: 10.3390/catal11010037
|View full text |Cite
|
Sign up to set email alerts
|

Sulfuric Acid Treated g-CN as a Precursor to Generate High-Efficient g-CN for Hydrogen Evolution from Water under Visible Light Irradiation

Abstract: Modifying the physical, chemical structures of graphitic carbon nitride (g-CN) to improve its optoelectronic properties is the most efficient way to meet a high photoactivity for clean and sustainable energy production. Herein, a higher monomeric precursor for synthesizing improved micro-and electronic structure possessing g-CN was prepared by high-concentrated sulfuric acid (SA) treatment of bulk type g-CN (BCN). Several structural analyses show that after the SA treatment of BCN, the polymeric melon-based st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Within the visible light range, B-ZCS v /Cd-T presented enhanced absorption ability compared with that of pure ZCS. Additionally, as the NaBH 4 treatment temperature gradually increases to 500 °C, a progressive red shift of the absorption edge was observed, indicating the homogeneous generation of boron dopants and sulfur vacancies defects in B-ZCS v /Cd-T. 35 The band gap energy of the photocatalysts was then calculated using the Kubelka−Munk transformation (shown in the Supporting Information). 36 According to the transformation, the band gaps progressively narrowed from 2.57 eV for ZCS to 2.41 eV for B-ZCS v /Cd-500 (Figure 3b), suggesting that the defect-or dopant-related mid gap states are introduced.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Within the visible light range, B-ZCS v /Cd-T presented enhanced absorption ability compared with that of pure ZCS. Additionally, as the NaBH 4 treatment temperature gradually increases to 500 °C, a progressive red shift of the absorption edge was observed, indicating the homogeneous generation of boron dopants and sulfur vacancies defects in B-ZCS v /Cd-T. 35 The band gap energy of the photocatalysts was then calculated using the Kubelka−Munk transformation (shown in the Supporting Information). 36 According to the transformation, the band gaps progressively narrowed from 2.57 eV for ZCS to 2.41 eV for B-ZCS v /Cd-500 (Figure 3b), suggesting that the defect-or dopant-related mid gap states are introduced.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The heptazine derivatives (also called tri- s -triazine or cyamelurine) and their cyamelurate analogs are quite versatile building blocks for the design of smart materials. 21 They are known to be precursors of graphitic carbon nitride (g-CN), 22 which photocatalysis the hydrogen (H 2 ) evolution reaction (HER) under visible light, 23–26 high energy materials, 27 liquid crystals, 28,29 and materials exhibiting nonlinear optical properties. 30 In recent years, cyamelurate ( Cy ) has attracted great interest owing to its nitrogen-rich system of three N-heteroaromatic rings fused in a planar conformation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the excessive consumption of fossil fuel has brought a series of severe environmental problems, thus it is very urgent to develop and utilize environmentally friendly and clean energy at present [1,2]. In the past decades, photocatalytic hydrogen production utilizing solar energy was considered to be a huge potential strategy for hydrogen generation [3][4][5]. It was reported that metal-free polymeric graphitic carbon nitride (i.e., g-C 3 N 4 ) possessed good visible light response activity, suitable position, and chemical stability, and thus can be a candidate for substituting the traditional expensive metal-based photocatalysts [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2009, Wang and co-researchers found that g-C 3 N 4 photocatalyst could split water to produce hydrogen under visible light [8]. Research about g-C 3 N 4 -based catalysts for photocatalytic hydrogen production is emerging and will continue to be attractive [3,4,9,10] in the coming years. Nevertheless, the bulk g-C 3 N 4 still has the following defects [9,10]: (1) small specific surface area; (2) scarce reaction active site; (3) insufficient visible light absorption (λ < 460 nm) ability and low quantum efficiency; and (4) high recombination rate of photo-generated electrons and holes.…”
Section: Introductionmentioning
confidence: 99%